Fluid Identity in The Elaborate Entrance of Chad Deity Play (2011) by Kristoffer Diaz - Maisya Noviana Nurafni; Delvi Wahyuni (Universitas Negeri Padang, 2021)
This thesis is an analysis of a play written by Kristoffer Diaz entitled The Elaborate Entrance Of Chad Deity (2011). It investigates the issue of fluid identity that is experienced by citizen in multicultural society. This analysis is related to the multiculturalism approach and the concept of fluid identity by Andrew Robinson and Leary and Tangney. The analysis focuses on the issue of fluid identity. The aim of this analysis is to what extent the character, conflict (plot), setting and stage direction contribute to reveal the issue of fluid identity. The result of the study shows that identity is fluid and dynamics. It is not biologically. Identity can be changed by time and contexts. Fluid identity is influenced by external factors.